Roles of Law on Medical Records for Data and Information Security: A Systematic Literature Review - Ida Bagus Udayana Hanggara; Tuty Kuswardhani; I Gusti Agung Gede Utara Hartawan (Journal of Law, Politic and Humanities, 2025)
Electronic medical records must adhere to the principles of data and information security, which include availability, integrity, and confidentiality. Medical records serve as legitimate legal evidence, thereby satisfying these principles both individually and institutionally. Consequently, the aim of this research is to explore the roles of law on medical records for data and information security. To achieve this aim, a systematic literature review (SLR) was employed. The Scopus and PubMed databases were chosen for their global recognition. Full-text articles from these databases were subjected to PRISMA analysis using Mendeley Reference Manager. The researchers collected 32 research articles by the categories of data protection law, medical records' law enforcement, and data protection law recommendation. The research findings indicate that the roles of law deal with the role of law in compliance and data protection, law enforcement and sanctions, a recommendation for improving compliance and data protection. In addition, the law is crucial for ensuring compliance and data protection in electronic medical records implementation in hospitals. However, compliance levels have not reached optimal levels. To improve security, awareness, and enforcement, collaboration with legal bodies, and educational initiatives are needed. Legislation like HIPAA and GDPR influence data protection measures, but penalties are insufficient. To enhance compliance, medical personnel should undergo rigorous training and improve oversight of health data management procedures